Implementasi Strategi Dinas Keluarga Berencana Pemberdayaan Perempuan dan Perlindungan Anak dalam Pengembangan Gerakan Perlindungan Anak Terpadu Berbasis Masyarakat di Kabupaten Serang - Alvina Cahya Winanti; Listyaningsih (Epistemik Press, 2023)
The Community-Based Integrated Child Protection Movement is one of the programs owned by the Serang Regency DKBPPPA regarding efforts to prevent children from acts of violence. The PATBM movement is a movement created by the Indonesian Ministry of Women's Empowerment and Child Protection which is run by communities in the form of groups living at the village or sub-district level. The problems found in this research were cases of child violence in Serang Regency which were high in the last three years (2020-2022), the PATBM movement which only existed in 68 villages out of a total of 326 villages in Serang Regency, the absence of direct socialization from the Regency DKBPPPA Serang is related to the introduction of the PATBM Movement in the community, the lack of commitment from stakeholders regarding the PATBM Movement in Serang Regency, the implementation of the PATBM Movement and the budget which is carried out simultaneously with other programs. The theory used is Strategic Management theory in the Strategy Implementation dimension according to Wheelen and Hunger (2014:11) which has three indicators, namely program, budget and procedures using descriptive qualitative research methods. From this research it is known that the strategy carried out by the Serang Regency DKBPPPA in developing the PATBM Movement is quite good by collaborating with government and non-government institutions. The form of activities carried out is by forming, coaching, evaluating, and monitoring. Meanwhile, activities in the community are handed over to each village that has been formed. Then, regarding the uncertain and limited budget. This makes the Serang Regency DKBPPPA direct the use of village funds for implementing PATBM activities in the community. And for DKBPPPA procedures, Serang Regency follows guidelines from the center and does not have special procedures.